Queen's Park Hotel, Trinidad, B.W.I. - 102 - (:unkn) unknown (Photogelatine Engraving Co. Limited, 2010)
This postcard shows the front of the Queen's Park Hotel which is located opposite the south section of the Queen's Park Savannah, Port of Spain, Trinidad. Originally built in 1893, this reconstruction completed in 1937 saw the centrepiece of the original hotel being demolished and a modern Art Deco structure with five floors taking its place. There is a line of taxis parked outside the building. The postcard is addressed to Mrs. G Gaskill of New Jersey, United States of America and affixed is 4 cents Trinidad and Tobago postage stamp.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Hotels--Trinidad and Tobago; 1951; Buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Historic hotels--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Architecture--Trinidad and Tobago; Roads--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Transportation--Trinidad and Tobago; Taxicab industry--Trinidad and Tobago; Taxicabs--Trinidad and Tobago; Roads--Guard fences; Balconies--Trinidad and Tobago; Trees--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)